2012
DOI: 10.1186/1465-9921-13-64
|View full text |Cite
|
Sign up to set email alerts
|

A Newfoundland cohort of familial and sporadic idiopathic pulmonary fibrosis patients: clinical and genetic features

Abstract: BackgroundIdiopathic pulmonary fibrosis (IPF) is an adult-onset Idiopathic Interstitial Pneumonia (IIP) usually diagnosed between age 50 to 70 years. Individuals with Familial Pulmonary Fibrosis (FPF) have at least one affected first or second-degree relative and account for 0.5-20% of cases.MethodsWe ascertained and collected DNA samples from a large population-based cohort of IPF patients from Newfoundland, Canada. For each proband, a family history was documented and medical records were reviewed. Each prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
1
15

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 33 publications
2
48
1
15
Order By: Relevance
“…A recent study reported that 3 of 38 familial probands and none of 50 sporadic cases studied manifested TERT/TR mutations. The three familial TERT mutation carriers exhibited shortened telomeres, but telomere lengths in all other samples from subjects without mutations were not measured (36). These reports indicate that a minority of cases with IPF exhibit telomere shortening, most of which is not associated with TERT or TR mutations.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…A recent study reported that 3 of 38 familial probands and none of 50 sporadic cases studied manifested TERT/TR mutations. The three familial TERT mutation carriers exhibited shortened telomeres, but telomere lengths in all other samples from subjects without mutations were not measured (36). These reports indicate that a minority of cases with IPF exhibit telomere shortening, most of which is not associated with TERT or TR mutations.…”
Section: Discussionmentioning
confidence: 74%
“…The incidence of shortening in the samples reported here was less than 6%, which may reflect the different population samples studied. The present study investigated the telomere lengths in a Mexican cohort, whereas other studies reported on samples collected in the United States or Canada (12,36). The patients with IPF in this study were of the sporadic type, with no genetic information available.…”
Section: Discussionmentioning
confidence: 99%
“…In most series, the evolution of FPF was comparable to that of IPF sporadic forms and the causes of death were similar to those observed with IPF sporadic forms [22][23][24]. As observed in sporadic pulmonary fibrosis, a definite radiological or histological UIP pattern is associated with poor prognosis in FPF [16,21].…”
Section: Radiographic and Pathological Pattern And Evolutionmentioning
confidence: 67%
“…Mutations in DKC1, NAF1 and TINF2 are much rarer (figure 1) [9,23,[28][29][30][31][32][33][34][35]. TERT or TERC mutations may be found in about 1-3% of sporadic IPF cases [28].…”
Section: Asymptomatic Involvementmentioning
confidence: 99%
See 1 more Smart Citation